“Savage nations roam o’er native wilds”:: Charles Mair and the Ecological Indian - Grubisic, Katia (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Charles Mair portrays the First Nations people as embodying the intersection point between ecology and race. In Tecumseh, Mair contrasts their communal connection with nature with the devastating effects of their political mistreatment. His poem "The Last Bison" is a dual narrative of dispossession, showing how both the First Nations peoples and the buffalo were reduced to servile scarcity. The implied sensitivity of these works seems incommensurable with Mair's employment as a government agent participating in the Western expansionist movement that was directly responsible for the destruction of First Nations people. The critical examination of this paradox in Mair's life and work illuminates his efforts to reconcile civilization and wilderness even if he cannot offer any feasible solution. However, it is significant that Mair's poetry performs a nuanced dialogue that others his subject while simultaneously allowing the other a voice, elevating his work beyond a narrative of dispossession to one of possession.